The Correlation between HbA1c and MCP-1 Levels in Diabetic Retinopathy Patients - Lestari, Anak Agung Wiradewi; Nabu, Ekarini Katharina Yunarti; Triningrat, Anak Agung Mas Putrawati; Wande, I Nyoman; Wirawati, Ida Ayu Putri; Mahartini, Ni Nyoman; Cong, Tzeto Han; Prabawa, I Putu Yuda (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2025)
Diabetic Retinopathy (DR) is a common microvascular complication of diabetes mellitus and a leading cause of vision loss. Persistent hyperglycemia plays a central role in the pathogenesis of DR by promoting chronic inflammation. Monocyte Chemoattractant Protein-1 (MCP-1), a key pro-inflammatory chemokine, is believed to mediate this process. This study aimed to investigate the correlation between glycemic control, as reflected by glycated hemoglobin (HbA1c) levels, and serum MCP-1 concentrations in patients with DR. A cross-sectional analysis was conducted involving 45 DR patients at Prof. dr. I. G. N. G. Ngoerah General Hospital. HbA1c levels were assessed enzymatically and reported in NGSP units, while serum MCP-1 concentrations were measured through ELISA and expressed in pg/mL. The correlation between the two parameters was evaluated using Spearman's rank correlation test, with significance determined at p <0.05.The participants consisted of 64.4% males and 35.6% females, with a mean age of 55.0±6.6 years. The median HbA1c was 9.5% (range: 5.9–12.3%), and the median MCP-1 level was 320.57 pg/mL (range: 32.34–605.41 pg/mL). A moderate positive correlation was identified between HbA1c and MCP-1 levels r = 0.45; p = 0.007). These findings indicate that increased blood glucose levels may coincide with elevated MCP-1, suggesting an ongoing inflammatory response contributing to DR progression. This study demonstrates a significant moderate positive correlation between HbA1c and serum MCP-1 in DR patients, suggesting that elevated blood glucose levels may contribute to increased MCP-1 expression. These findings support the potential role of MCP-1 as a biomarker of both poor glycemic regulation and inflammation in the progression of diabetic retinopathy.